Immunomodulatory Effect of Phage Depolymerase Dep_kpv74 with Therapeutic Potential Against K2-Hypervirulent Klebsiella pneumoniae - Nikolay V. Volozhantsev; Maria A. Makarova; Alena S. Kartseva; Marina V. Silkina; Valentina M. Krasilnikova; Egor A. Denisenko; Alexander I. Borzilov; Victoria V. Firstova (Antibiotics)
Background: The emergence of multidrug-resistant hypervirulent Klebsiella pneumoniae (hvKp) has made it difficult to treat and control infections caused by this bacterium. Previously, the therapeutic effectiveness of phage-encoded depolymerase Dep_kpv74 in a mouse model of K. pneumoniae-induced thigh soft tissue infection was reported. In this study, the effect of Dep_kpv74 on blood parameters in mice, the proliferation and subpopulation composition of spleen lymphocytes, and the activity and stability of the enzyme at different pH and temperatures were further explored. Results: The stability tests showed that Dep_kpv74 remained active in the temperature range from 8 °C to 55 °C. The optimal pH value for maintaining the activity of Dep_kpv74 ranged from 5.0 to 9.0. The depolymerase was detected in the blood, spleen, and lungs of mice 10 min after intraperitoneal administration, reaching maximum activity values after 1–3 h and maintaining activity a day after administration. The introduction of Dep_kpv74 at the therapeutic dose (10 μg/mouse) or at a 10-fold higher dose did not lead to reliable changes in bloodstream cell content compared with the reference values of intact mice. The biochemical results of the studies indicated that Dep_kpv74 did not exert any toxic effects on liver and kidney functions. The results of the analysis of lymphocyte proliferative activity demonstrated that Dep_kpv74 depolymerase has a mild immunomodulatory effect. Conclusions: Thus, the results of this study provide one more confirmation that depolymerase Dep_kpv74 is a potential candidate for the treatment of infections caused by hvKp expressing K2 capsular polysaccharides.